Politica și politheia în proverbele românești din secolul al XVIII-lea - Laura Bădescu (Revista de Istorie și Teorie Literară)
The paper proposes an analysis of the concept “politheia” in relation with Romanian paremiological corpus used in the eighteenth century. In this framework, three contexts (genetic, generic and functional) were described. They caused mutations in the semantic of paremiological structures. The intention is to explain these changes by highlighting the connections between sentential statements and the political, social and cultural zeitgeist.